Effects of cationic porphyrins as G-quadruplex interactive agents in human tumor cells - IZBICKA, E; WHEELHOUSE, R. T; RAYMOND, E; DAVIDSON, K. K; LAWRENCE, R. A; SUN, D; WINDLE, B. E; HURLEY, L. H; VON HOFF, D. D (Cancer research (Chicago, Ill.), 1999)
A series of cationic porphyrins has been identified as G-quadruplex interactive agents (QIAs) that stabilize telomeric G-quadruplex DNA and thereby inhibit human telomerase; 50% inhibition of telomerase activity was achieved in HeLa cell-free extract at porphyrin concentrations in the range < or = 50 microM. Cytotoxicity of the porphyrins in vitro was assessed in normal human cells (fibroblast and breast) and human tumor cells representing models selected for high telomerase activity and short telomeres (breast carcinoma, prostate, and lymphoma). In general, the cytotoxicity (EC50, effective concentration for 50% inhibition of cell proliferation) against normal and tumor cells was > 50 microM. The porphyrins were readily absorbed into tumor cell nuclei in culture. Inhibition of telomerase activity in MCF7 cells by subcytotoxic concentrations of TMPyP4 showed time and concentration dependence at 1-100 microM TMPyP4 over 15 days in culture (10 population doubling times). The inhibition of telomerase activity was paralleled by a cell growth arrest in G2-M. These results suggest that relevant biological effects of porphyrins can be achieved at concentrations that do not have general cytotoxic effects on cells. Moreover, the data support the concept that a rational, structure-based approach is possible to design novel telomere-interactive agents with application to a selective and specific anticancer therapy.